(untitled) (Public Sector Economics - submission site, 2020)
In this paper, we provide the first analysis of the level and determinants of sovereign exposure of banking systems in Central and Eastern European (CEE) countries, thus contributing to the existing literature on sovereign exposures and the sovereign-bank nexus. Results of descriptive analysis showed that exposure to sovereign debt securities in CEE countries is substantially higher than in euro area countries, which can be explained by the lower development of financial markets in this region. We also found evidence of home-bias in CEE and emphasized the role of different monetary policy regimes in explaining differences in exposure among CEE countries. Results of panel analysis showed that changes of debt securities in bank balance sheets in CEE countries are mostly determined by broader macroeconomic conditions and to a lesser extent by their regulatory frameworks. In addition, we did not find evidence of so-called reach-for-yield behaviour.